Pengaruh Kompensasi, Kepuasan Kerja Karyawan dan Mutu Produk terhadap Penjualan Parfum pada PT Aura Essence Indonesia (Studi Kasus pada Outlet Penerbangan Internasional dan Domestik Bandar Udara Soekarno-Hatta) - esaka pratala kinkin (Jurnal MoZaiK, 2019)
ABSTRACT The object of this research was carried out at the Indonesian Aura Essence Company Domestic and International Aviation Division, where a sample of 60 employees was in the Domestic and International Aviation Division. This study uses a quantitative method to answer the problem formulation and prove the research hypothesis proposed. The data analysis technique used consisted of inferential statistical data analysis techniques including product moment correlation analysis and multiple correlation, coefficient of determination analysis technique, and simple regression analysis and multiple regression techniques. The results of testing the hypothesis, that the independent variables (compensation X1, job satisfaction X2 and product quality X3) have a significant effect on perfume sales at PT. Aura Essence, for compensation variable X1 and job satisfaction X2 has a significant effect on sales, while product quality has no significant effect because consumers basically already have confidence in the quality of products sold by the Indonesian Aura Essence Company. The author gives one suggestion that the company can maintain the quality of perfume products sold and add a brand of perfume that is needed more by consumers such as perfume with the brand Bond 9, Creed, Ninaricci, Balenciaga and so on, especially the latest perfumes that are not only sold in international divisions but it is also sold in the domestic flight division. In addition, to find out more details about the variables that can affect sales volume, the authors suggest that further research from the results of this study. Keywords: Compensation, job satisfaction, product quality and sales